Effectiveness of Banana Blossom on Breast Milk Production in Breastfeeding Mothers - Rani Safitri; Siti Salma Karim; Rosyidah Alfitri (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Exclusive breastfeeding for the first six months is one of the most valuable investments in a child’s health, growth, and intelligence, yet ensuring sufficient breast milk production can be a challenge for some mothers. The banana heart, or banana flower, is an inexpensive and easily accessible part of the banana plant traditionally used to enhance lactation. Rich in fiber, vitamins, and minerals, it is believed to support maternal health and stimulate milk production. This study aimed to determine the effect of banana heart consumption on the average increase in breast milk production among breastfeeding mothers in the Bahari Health Center Working Area. A quasi-experimental design with a pretest–posttest control group was employed, involving breastfeeding mothers divided into treatment and control groups. The treatment group consumed banana heart preparations, while the control group maintained their regular diet. Breast milk production was measured before and after the intervention. Results indicated that, before treatment, the average breast milk production in the treatment group ranged from 401–500 cc, with a mean of 496.67 cc. After consuming banana heart, production significantly increased to 801–900 cc, with a mean of 816.67 cc. In contrast, the control group’s production remained between 401–500 cc, with a mean of 453.33 cc, showing no significant change. Statistical analysis confirmed the positive effect of banana heart consumption on increasing breast milk production. In conclusion, banana heart can be considered an effective, low-cost, and locally available dietary intervention to improve lactation outcomes, supporting the practice of exclusive breastfeeding for six months. Public health initiatives could promote the use of banana heart as a natural approach for mothers experiencing lactation challenges.